2013
DOI: 10.3174/ajnr.a3595
|View full text |Cite
|
Sign up to set email alerts
|

Improved T2* Imaging without Increase in Scan Time: SWI Processing of 2D Gradient Echo

Abstract: BACKGROUND AND PURPOSE: 2D gradient-echo imaging is sensitive to T2* lesions (hemorrhages, mineralization, and vascular lesions), and susceptibility-weighted imaging is even more sensitive, but at the cost of additional scan time (SWI: 5-10 minutes; 2D gradient-echo: 2 minutes). The long acquisition time of SWI may pose challenges in motion-prone patients. We hypothesized that 2D SWI/phase unwrapped images processed from 2D gradient-echo imaging could improve T2* lesion detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Another interesting observation was that only 70% of the iron laden lesions demonstrated hypointense signal on GRE-T2* weighted images whereas 98% of the lesions showed hypointensity on SWI in spite of similar slice thickness and in-plane resolution for both these images. In accordance to previous studies 31,32 , our observation suggests that SWI is more sensitive to susceptibility effects than GRE-T2* weighted images probably because SWI combines information both from phase and magnitude images to ascertain the local susceptibility changes among neighboring tissues whereas susceptibility contrast on GRE-T2* is mainly dependent on a combination of spin-spin relaxation (T2) and magnetic field inhomogeneity. We believe that inclusion of phase information renders SWI more sensitive to susceptibility effects than GRE-T2* images.…”
Section: Discussionsupporting
confidence: 91%
“…Another interesting observation was that only 70% of the iron laden lesions demonstrated hypointense signal on GRE-T2* weighted images whereas 98% of the lesions showed hypointensity on SWI in spite of similar slice thickness and in-plane resolution for both these images. In accordance to previous studies 31,32 , our observation suggests that SWI is more sensitive to susceptibility effects than GRE-T2* weighted images probably because SWI combines information both from phase and magnitude images to ascertain the local susceptibility changes among neighboring tissues whereas susceptibility contrast on GRE-T2* is mainly dependent on a combination of spin-spin relaxation (T2) and magnetic field inhomogeneity. We believe that inclusion of phase information renders SWI more sensitive to susceptibility effects than GRE-T2* images.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, as SWI is more susceptible to artifacts caused by calvaria, susceptibility artifacts arising from field inhomogeneities at the interfaces between bone and tissue, the detection of small SAH and SDH may be limited. Soman et al reported that GRE was superior to SWI with regard to T2* lesion conspicuity in one case with cortical venous thrombosis due to worsened calvarial artifacts adjacent to the T2* lesion [33].…”
Section: Discussionmentioning
confidence: 99%
“…Like other neuroimaging studies evaluating cerebral microhemorrhage presence, this study used an accepted GRE imaging sequence as the reference standard for CMH presence 8, 15, 27, 28 . Here, the three echoes of the 3D GRE magnitude images were used as ground truth for the presence of CMHs, given that direct pathological correlation was not possible (as is the case in many clinical imaging studies).…”
Section: Discussionmentioning
confidence: 99%